Trends and issues in doctoral education : A global perspective - Yudkevich, Maria, Ed.; Yudkevich, Maria; Altbach, Philip G; de Wit, Hans; Sage Publications (New Delhi, Sage, 2020)
"Doctoral education is of prime importance worldwide. In some countries, there is severe shortage of doctoral degree holders, while in others there is an oversupply in many fields. There is a global debate on the best ways of providing doctoral training. To illustrate global trends, the book analyses the current realities of doctoral education with the help of 15 case studies based on different countries and regions. It includes an overview of the state of the literature on doctoral education as well as an analysis of doctoral education from a historical perspective with a detailed comparative discussion. Trends and Issues in Doctoral Education: A Global Perspective also examines the challenges and ideas of current and proposed reforms in doctoral education"--
Includes bibliographical references and index.
Keywords: Universities and colleges -- Ratings and rankings -- Case studies; Education, Higher -- Aims and objectives -- Case studies; Education and globalization -- Case studies; Higher education and state -- Case studies